Multinational banks and development finance - Christian E. Weller; Mark J. Scher (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
Financial market recommendations for less industrialized economies, particularly in the wake of the recent financial crises, have included a push for more international financial competition. The entry of multinational banks (MNBs) into developing economies is supposed to create more market discipline for domestic banks, thus making them more efficient, and enhancing financial stability. Using data from the BIS and the IMF, we look at the determinants of MNB presence, at MNB activities, and their impact on credit supply and on financial stability. With respect to the determinants of MNB presence, we find that lower asset prices, a ready market and competition with other MNBs matter more than economic fundamentals of the host economy. In line with these results, MNBs focus their activities predominantly on serving MNCs, and on providing services that domestic banks cannot offer to domestic corporations, and high net worth individuals. Thus, we also find that domestic banks lower their total credit exposure by reducing their commercial loans in response to increased competition, particularly in serving MNCs, domestic corporations, or high net worth individuals, which may lead to real implications for less industrialized economies, particularly lower business investment.
Keywords: 330